PENGEMBANGAN EKSTRAKURIKULER PAI: Studi Kasus SMAN I Mataram, NTB - Suprapto Suprapto (EDUKASI: Jurnal Penelitian Pendidikan Agama dan Keagamaan, 2013)
The objectives of this study are to determine: 1) efforts the schools have made in developing the studentsâ€™ religious extracurricular activities internally while ascertaining the types of religious extracurricular activities at schools, 2) influencing factors to the implementation of such extracurricular programs. This study was conducted in SMA Negeri 1 Mataram, West Nusa Tenggara, during which a descriptive analytic method was used and the data were collected through questionnaires, interviews in addition to observation and manuscript study. The results show that extracurricular activities conducted in the target school involved quite a diverse religious activity which includes: Holy Qurâ€™an recitation at the beginning of each class, midday prayer in congregation, congregated prays to open and conclude each class, congregated Friday sermon, Qurban sacrifice festivity, and organization of varied activities commemorating the Islamic Holidays (PHBI)â€ and more. In addition, two major reasons had influenced the studentsâ€™ participation in these extracurricular programs, which are classified as (a) internal and (b) external factors. The first includes spiritual, social, and personal motives. And the second relates to these very extracurricular activities ranging from the program, material, method, tutor, to teacherâ€™s stimulus.Â Tujuan penelitian ini adalah untuk mengetahui: 1) upaya-upaya yang dilakukan oleh sekolah dalam mengembangkan aktivitas ekstrakurikuler keagamaan siswa di sekolah, mengetahui jenis aktivitas ekstrakurikuler keagamaan di sekolah, 2) faktor-faktor yang mempengaruhi pelaksanaan program ekstrakurikuler keagamaan siswa di sekolah. Lokasi penelitian dilakukan di SMA Negeri 1 Mataram, Nusa Tenggara Barat. Penelitian ini bersifat deskriptif analitik, dengan teknik pengumpulan datanya melalui angket, wawancara, observasi dan studi dokumen. Hasil penelitian menunjukan bahwa kegiatan ekstrakurikuler yang dilakukan di sekolah sasaran penelitian terdapat cukup beragam kegiatan keagamaan seperti: membaca Al-Qurâ€™an pada awal jam pelajaran, sholat dzuhur bersama, berdoâ€™a bersama-sama dalam memulai dan mengakhiri pelajaran, sholat jumâ€™at bersama, pemotongan hewan Qurban, serta menyelenggarakan kegiatan â€œpada peringatan hari-hari besar Islam (PHBI)â€ dan lain-lain. Selain itu terdapat dua faktor utama yang berpengaruh terhadap keikutsertaan siswa dalam program ekstrakurikuler keagamaan, yaitu; (a) internal, dan (b) eksternal. Faktor internal, antara lain; motif keagamaan, motif sosial, dan motif pribadi. Sedangkan faktor eksternal, berkenaan dengan kegiatan ekstrakurikuler keagamaan itu sendiri, seperti; program, materi, metode, pembimbing, dan dorongan guru.